2008
DOI: 10.1021/jp711902p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen−Deuterium Exchange in Bulk LiBH4

Abstract: Because of its apparent simplicity, diffusion of hydrogen in solids can be regarded as a general model system for diffusion. However, only rudimentary knowledge exists for the dynamics of hydrogen in complex hydrides. Insight into the specific diffusion process is given by hydrogen-deuterium exchange experiments. Thermogravimetry and Raman spectroscopy are used to measure the hydrogen-deuterium exchange during the decomposition of LiBH4. At a temperature of 523 K the self-diffusion constant of deuterium in LiB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 31 publications
7
65
2
Order By: Relevance
“…We consider later (see below) the question of whether the diffusing units are BH 4 molecular anions or H anions, as has been suggested. 15 Here we simply remark that either motion will fully average to zero all of the hydrogen dipolar interactions. Related two-step narrowing appears 24 in LiH.…”
Section: Resultsmentioning
confidence: 97%
“…We consider later (see below) the question of whether the diffusing units are BH 4 molecular anions or H anions, as has been suggested. 15 Here we simply remark that either motion will fully average to zero all of the hydrogen dipolar interactions. Related two-step narrowing appears 24 in LiH.…”
Section: Resultsmentioning
confidence: 97%
“…The idea that B atoms are involved in the translational motion on the NMR time scale is supported by the observation [15,24] that the 11 B line width drops below the value expected for the B-B contribution to the 'rigid lattice' width. It should be noted that recent Raman scattering measurements of the H-D exchange in the high-T solid phase of LiBH 4 [30] have been interpreted in terms of individual hydrogen atoms moving from one BH 4 group to another. However, estimates of the local H exchange rate between BH 4 groups based on the 11 B NMR experiments in the liquid phase of LiBH 4 [31] have shown that near the melting point this rate is lower than 1 s −1 .…”
Section: Translational Diffusion Of LI + and (Bh 4 ) − Ions In The Himentioning
confidence: 99%
“…[82]), in liquid LiBH 4 (stretching vibrations measured by Raman spectroscopy, Ref. [83]), in LiBH 4 dissolved in organic solvents (stretching vibrations measured by IR spectroscopy, Ref. [84]) and in solid LiBH 4 [62].…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%
“…Hydrogen.deuterium exchange probed by vibrational spectroscopy is also used to probe the hydrogen transport mechanism in tetrahydroborates: recently we evidenced the presence of all partially exchanged BH 4-n D n units (0 < n < 4) in LiBH 4 exposed to deuterium gas below the melting temperature [83,88].…”
Section: Sorption Mechanism Of Complex Hydrides Probed By Vibrationalmentioning
confidence: 99%